Phosphorus influence Cd phytoextraction in Populus stems via modulating xylem development, cell wall Cd storage and antioxidant defense. (March 2020) - Yang, Can; Qiu, Wenwen; Chen, Zexin; Chen, Wenyi; Li, Yunfei; Zhu, Jingle; Rahman, Siddiq Ur; Han, Zixuan; Jiang, Yun; Yang, Guijuan; Tian, Jing; Ma, Qin; et al.
Abstract: The soils in mining lands with cadmium (Cd) contamination usually are deficient in nutrients. Disclosing how P nutrition and N:P stoichiometric ratio influences Cd accumulation and stress tolerance in stems of Populus spp. will facilitate the phytoremediation of mining sites polluted by Cd. In this study, investigations at the anatomical and physiological levels were conducted using a clone of Populus × euramericana . Both phosphorus deficiency and cadmium exposure inhibited xylem development via reducing cell layers in the xylem. Under P-sufficient condition, appropriate P status and balanced N:P ratio in stem promoted xylem development under Cd exposure via stimulating cell division, which enhanced Cd accumulation in stems. Cd accumulation in cell walls of collenchyma tissues of the stem was enhanced by P application due to increased polysaccharide production and cell wall affinity for Cd. The low P concentrations (0.3–0.4 mg g −1 ) and imbalanced N:P ratio under P deficiency inhibited the production of APX and ascorbate–GSH cycle, which increased oxidative stress and lipid peroxidation as indicated by high MDA concentration in stem. Under P-sufficient condition, the interactions between phytohormones and antioxidants play crucial roles in the process of antioxidant defense under Cd exposure. In conclusions, appropriate P addition and balanced N:P ratio enhanced secondary xylem development and promoted cadmium accumulation and stress tolerance in Populus stems, which can benefit the phytoextraction of Cd from Cd-contaminated soil. Graphical abstract: Image 1 Highlights: Sufficient tissue P concentration and balanced N:P ratio enhanced cell division in stem. Low tissue P concentration and imbalanced N:P ratio inhibited xylem development. Phosphorus increased cell wall affinity for Cd and Cd accumulation in cell wall in stem. P deficiency decreased phytohormone levels and increased oxidative stress in stem. Phosphorus enhanced Cd phytoextraction via promoting xylem development and antioxidant defense.